Factors Influencing Maternal Behavior Towards The Accuracy Of Antenatal Care Visits At Bulurokeng Health Center In 2020 - Najdwah Emilia; Purnamaniswaty Yunus; Azizah Nurdin; Arlina Wiyata Gama; Siti Aisyah Kara (Jurnal Life Birth, 2023)
Maternal mortality is death caused by all things related to and or aggravated by pregnancy and its handling, while one of the efforts to reduce maternal mortality is to conduct a complete ANC examination and in accordance with established integrated standards. This study aims to determine the factors that influence the accuracy of Antenatal Care visits at the Bulurokeng Health Center, Biringkanaya District, Makassar City, South Sulawesi in 2020. This type of research is using observational design with quantitative survey research methods. The approach taken in this study was Cross Sectional. The population studied was mothers who had conducted ANC examinations at the Bulurokeng health centre for the January - December 2020 visit period, totalling 302 mothers. The sampling technique used was simple random sampling with a total sample of 100 mothers and the results were processed using SPSS with the chi-square test. The study obtained a p-value of 0.001 (<0.05) for the knowledge variable on the accuracy of ANC visits. The p-value is 0.029 (<0.05) for the attitude variable on the accuracy of ANC visits. The p-value is 0.032 (<0.05) for the variable of husband support on the accuracy of ANC visits. The p-value is 0.041 (<0.05) for the affordability variable on the accuracy of ANC visits. The meaning of this value is that there is a relationship between the variables of knowledge, attitude, husband's support, and affordability to the accuracy of ANC visits.